EFFICIENCY OF THERMOELECTRIC GENERATORS MODULE METHODS OF INCREASE (Web of Technology: Multidimensional Research Journal, 2024)
It is known that many scientists are currently conducting a lot of research on the development of energy obtained in an ecologically clean way. In this regard, thermoelectric generators that convert heat directly into electricity are also of particular importance. The advantage of thermoelectric generators is that the device does not require any moving and frictional parts, high pressure conditions and specific situations. They are long-lasting and require no maintenance. The disadvantage is its extremely low useful work coefficient value (0.8~1%).